Milk sheep quality variations during lactation in grazing and confined reared ewes - Pistoia A.; Poli P.; Casarosa L.; Balestri G.; Ferruzzi G. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
The present study aims to investigate the effects of different sheep rearing techniques on the milk qualitative variation. The trial involved 2 groups of 10 ewes, half of them primiparous, reared by two different techniques: (i) grazing system group with concentrate integration 0.6 kg/kg of milk; and (ii) confined rearing group with hay ad libitum and the same quantity of concentrates. Milk yield and quality have been controlled monthly by collecting individual milk samples, which have been analysed in their physical, chemical and technological characteristics. The confined ewes produced a higher milk quantity during the whole lactation period (163 days). Chemical milk characteristics resulted better in the grazing group, because of the higher values of fat, protein and casein percentage, while the milk of confined ewes was more acid. The higher acidity values for milk of the confined group determined a better rennet clotting time r, while the grazing group produced a harder curd firmness a30, 30 min after rennet addition. The outlines of qualitative parameters during lactation were similar in the two groups: the chemical characteristics improved during lactation, while the curdling aptitude was better in the intermediate period.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)